Primary Desmoplastic Melanoma of the Penis - Julia T. Chu; Michael A. Liss; William W. Wu; Atreya Dash; Di Lu (Case Reports in Urology, 2015)
Desmoplastic melanomas are rare amelanotic melanomas that usually occur on skin with sun exposure. In this report, we present a 72-year-old man who presented with a desmoplastic melanoma of the penis. To our knowledge this represents the first reported case of primary desmoplastic melanoma of the penis. We discuss the pathologic differential and histologic evaluation.